Personal Transferable Skills and the LIS Profession - Sharma, Jaideep (Journal of Information and Knowledge, 1999)
Personal Transferable Skills (PTS) are those skills that enable a library professional to acquire, structure and interpret subject knowledge. Communication skills, ability to work in groups, problem solving, and interpersonal skills are the basic facets of PTS. The paper discusses the importance of there skills in the library and information profession.